Duration of life-cycle of three parasitic hymenoptera on Saissetia oleαe (Bernard) growing on two different host plants. - Macropodi, M.V. (ENTOMOLOGIA HELLENICA, 1985)
In this work the duration of the life-cycle of Metaphycus helvolus (Comp.) (parasite mainly on the third stage), Μetaphycus affinis stanley (Comp.) (parasite mainly on the third stage) and Μetaphycus lounsburyi (How.) (parasite mainly on the fourth stage) (Hymenoptera: Encyrtidae) on S. οleae, developed on different substrates, i.e. potato sprouts and plants of Nerium oleander, under laboratory conditions was determined. Among the Hymenoptera parasitizing S. oleae on Corfu, M, helvolus and M. lounsburyi, are of particular importance M. affinis stanley was introduced in Corfu in 1976 and despite the fact that the population of S. οleae in the release area was practically eliminated from other factors shortly after the release of the parasite, there is evidence that the parasite was finally established. The above parasites can be successfully reared on S. οleae developed both on potato sprouts and Nerium oleander. The study was carried out at 23±1°C, 65-70% R.H. and 12 hours of artificial light per day. For each species, 3 potato sprouts and three plants of Nerium oleander in pots infested with S. οleae were placed in each 60X30X40 cm cage. The host insects were oviposited in by adult parasites introduced into the cages and left there for two days. The number of emerging adult parasites in each cage was recorded daily (a total number of adults emerged per cage varied from 23 to 195) and the time taken for 50% emergence was calculated from the correlation equation by plotting the cumulative percentage of adults emerged against time. For M. helvolus the mean duration time of the life cycle was estimated to be 19.4 days on scales developed on potato sprouts and 15.1 days on scales developed on N. oleander. For M. affinis stanley the relevant estimates were 18.8 days and 23.4 days, respectively, while for M. lounsburvi the estimates were 21.3 and 18.6 days, respectively. For M. helvolus and M. lounsburyi the duration of the life cycle was shorter when the host insect developed on Nerium plants than on potato sprouts. For M. affinis stanley the reverse was true. These differences show the effect of the host of S. oleae on the time of development of the parasites, possibly reflecting the differences of the scale insect developed on different hosts as food quality for the parasites.